DINAMIKA HUKUM ISLAM DAN PERUBAHAN SOSIAL DI ACEH (Upaya Membangun Hukum Pindana Islam yang Responsif Dan Dinamis) - Muhammad Rusdi bin Muhammaddiah; Muhazir (IAIN Langsa, 2021)
Changes in Islamic law can not be avoided, because Islamic law is in direct contact with a dynamic society. A society with a social background cannot avoid social symptoms when faced with Islamic law. Changes in Islamic law until now are still reaping the pros and cons between fundamentalist and contextualist groups, each of whom has its own views on Islamic legal texts. This study is a literature review with a conceptual approach. The results of this study indicate that the dynamics of changing Islamic law are strongly influenced by social dynamics. This is evident when Islamic law is exposed to a changing social reality. In order to accommodate social change, Islamic law, with the concept of maqasid sharia, is able to answer the needs of social law without having to leave the principles of sharia.